Performance Appraisal Practices and Teacher Performance in Public Secondary Schools in Kenya: A Case of Busia County - Khaemba, Pamela Naswa; Maiyo, Julius Kiprop Maiyo; Manini, Muganda Munir (Journal of Education and Practice, 2024)
Purpose: The purpose of the study was to investigate the relationship between performance appraisal practices and teacher performance in Busia County, Kenya. The Systems theory and the Ability-Motivation-Opportunity (AMO) theory informed this study. Methodology: The study was anchored on a pragmatic paradigm and adopted a mixed methods approach. The study targeted 185 public secondary schools in Busia County. The study categorized respondents into 3 strata: Principals, Mathematics Head of Department (HODs) and County Director of Education (CDE). Simple random sampling was then utilized to select samples from each stratum. Schools were clustered based on 7 Sub- Counties in Busia County. The sample size of the study was 126 HODs, 19 Principals and 1 CDE. Questionnaires and interview schedules were used to collect data. Piloting was conducted in 37 schools to refine instruments. Thematic analysis was applied in the analysis of qualitative data. Data analysis and interpretation was based on descriptive statistics such as frequencies, percentages, mean, standard deviation and inferential statistics such as correlation and regressions. Findings: The findings of the study was that there is a statistically significant relationship between performance appraisal and teacher performance (r = 0.440, p<0.05), hence the study rejected the null hypothesis. The study concluded that a unit improvement in performance appraisal is likely to result to an improvement in the teacher performance by 44% (b = 0.440, t= 0.855, p<0.05). The study holds substantial academic and policy implications. Unique Contribution to Theory, Practice and Policy: The findings contribute to the understanding of the complex relationships between performance appraisal practices and teacher performance. The study provides actionable insights for education managers, empowering them to take strategic measures to address performance gaps and improve teaching standards in the unique setting of public secondary schools in Kenya. By understanding the dynamics between performance appraisal practices and teacher performance, educational institutions can tailor strategies to optimize the effectiveness of their teaching staff in Science, Technology, Engineering and Mathematics STEM subjects.